Grid Synchronization and Control of a Doubly Fed Induction Generator (DFIG) Wind Turbine using Unified Power Flow Controller (UPFC) - C. Pacis, Michael; Mir, Iman (International Journal of Engineering and Technology, 2018)
Nowadays, wind energy conversion system (WECS) development becomes a necessity on a modern power system. Abundancy of these sources with the proper site selection, the WECS serves as an alternative source but with intermittency issues. In the case of connecting wind farms to the power system network, since regions with wind energy potential are not necessarily close to consumers, voltage stability and reactive power control are the most important issues. Using Flexible AC Transmission System (FACTS) devices are considered in order to maintain stability and provide the reactive power requirement of the grid and transfer the maximum power extracted from wind turbine to consumers. In this study, a wind farm used Doubly Fed Induction Generator (DFIG) modeled in MATLAB and synchronized to grid. Then, stability assessment is made for four different grid fault cases and each case is studied with and without Unified Power Follow Controller (UPFC) in the power network. Results are shown, after applying UPFC voltage transients where fault are decreased, wind turbine reactive power demand is eliminated, and wind turbine is able to provide a constant reactive power close to its nominal value.Â Â